Psikoedukasi Toxic Relationship: How to Get Rid of It? - Tri Sulastri; Novriana Luthfia Ramadhana; Nur Arrad Tenri Gangka; Nur Fitri Ramadani; Nur Hatria A; Nurul Mutmainna (Jurnal Pengabdian Masyarakat Bestari, 2022)
The purpose of the talk show is to conduct psychoeducation and increase public knowledge regarding toxic relationships. The method used is a quasi-experimental research. Prevention is carried out through the zoom meeting application by providing psychoeducation through a talk show which will be held on September 25 via zoom. The number of participants who took part in the talkshow were 120 people and as many as 77 people who filled out the pre-test and post-test. The instrument uses knowledge questions before (pre-test) and after (post-test) the treatment given. Data analysis techniques using quantitative methods with percentage techniques. The results show that most of the participants have a better understanding of toxic relationships. There is a psychoeducation effect on increasing participants' knowledge regarding toxic relationships.